Plant Chemical Genomics Methods and Protocols - Hicks, Glenn R.; Robert, Stéphanie; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2014)
Plant Chemical Genomics: Methods and Protocols , expert researchers in the field detail many of the techniques used for identification of bioactive compounds from a large selection of fields in plant biology including plant pathogenesis, immune responses, small RNA processing, endomembrane trafficking, lipids, plant hormone signaling and cell wall. The presentation of these and other examples as well as synthetic chemistry, computation and target identification provides a comprehensive overview of the practical aspects of chemical biology that are possible in plant systems. Small molecules and natural products that produce a phenotype in plants have been known for decades. The agrichemical industry has utilized small molecules based on known natural molecules such as auxins, cytokinins, abscissic acid and other growth regulators. In recent years, the screening and characterization of novel small molecules has enhanced our understanding of protein function, metabolic, signaling and endomembrane pathways, and their interactions in basic plant research. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.
Fully-automated Compound Screening in Arabidopsis thaliana Seedlings -- Time-profiling Fluorescent Reporters in the Arabidopsis Root -- Screening for Bioactive Small Molecules by in vivo Monitoring of Luciferase-based Reporter Gene Expression in Arabidopsis thaliana -- Application of Yeast-two Hybrid Assay to Chemical Genomic Screens: A High-throughput System to Identify Novel Molecules Modulating Plant Hormone Receptor Complexes -- High-throughput Screening of Small Molecule Libraries for Inducers of Plant Defense Responses -- Using a Reverse Genetics Approach to Investigate Small Molecule Activity -- Investigating the Phytohormone Ethylene Response Pathway by Chemical Genetics -- Screening for Inhibitors of Chloroplast Galactolipid Synthesis Acting in membrano and in Planta -- Forward Chemical Screening of Small RNA Pathways -- Identification and Use of Fluorescent Dyes for Plant Cell Wall Imaging Using High-Throughput Screening -- High-throughput Identification of Chemical Endomembrane Cycling Disruptors Utilizing Tobacco Pollen -- Plant Chemical Genomics: Gravity Sensing and Response -- Screening Chemical Libraries for Compounds that Affect Protein Sorting to the Yeast Vacuole -- The use of Multi-drug Approach to Uncover New Players of the Endomembrane System Trafficking Machinery -- Cheminformatic Analysis of High-Throughput Compound Screens -- Endomembrane Dissection Using Chemically-Induced Bioactive Clusters -- Statistical Molecular Design: A Tool to Follow Up Hits From Small Molecule Screening -- Early Stage Hit Triage for Plant Chemical Genetic Screens and Target Site Identification -- Screening for Gene Function using the FOX (Full-length cDNA OvereXpressor gene) Hunting System -- Quantification of Stable Isotope Label in Metabolites via Mass Spectrometry -- 1H NMR Based Metabolomics Methods for Chemical Genomics Experiments -- Determination of Auxin Transport Parameters on the Cellular Level -- Analyzing the in vivo Status of Exogenously Applied Auxins: A HPLC-based Method to Characterize the Intracellularly Localized Auxin Transporters.
Keywords: Plant science; Botany; Plant genetics; Plant Sciences; Plant Genetics and Genomics